Effects of early and late treatments of low-intensity, high-frequency mechanical vibration on bone parameters in rats. (2nd December 2015) - Sasso, Gisela Rodrigues da Silva; Florencio-Silva, Rinaldo; Santos, Miriam Aparecida; Teixeira, Cristiane de Paula; Daniele Reginato, Rejane; Simões, Manuel de Jesus; Katchburian, Eduardo
Abstract: Low-intensity, high-frequency mechanical vibration (LHMV) has shown to increase bone formation. However, studies comparing the effectiveness of early- and late-treatments of LHMV to counteract bone loss have not been documented. This study was designed to compare the effects of early- and late-treatments of LHMV (at 30 Hz/0.6 g, 20 min per day/five days per week, for 12 weeks) on bone parameters in ovariectomized (Ovx) rats. Thirty days after ovariectomy, 40 adult rats were randomly divided into four groups: GI (early control group); GII treated with LHMV 3 weeks after Ovx (early treatment); GIII (late control group) and GIV treated with LHMV twelve weeks after Ovx (late treatment). Bone mineral density (BMD) was analyzed before Ovx and after treatments. Then, animals were killed, and the femurs were collected and their length and diaphysis diameter were measured; the distal femurs were taken and processed for histomorphometry and polarized light microscopy for collagen fibers analysis or subjected to immunohistochemistry of cleaved caspase-3 in osteocytes. Statistical analysis was done by ANOVA followed by the Bonferroni post hoc test ( p <  0.05). BMD was similar among the groups before Ovx, but after treatments, it was significantly higher in GII and GIV compared with their control groups ( p <  0.05). Femur length and cortical bone thickness were similar among the groups, but the diaphysis diameter of GII was higher compared with GI. Trabecular bone area was higher in the vibrated groups, but it was greater in GII ( p <  0.05). Also, the vibrated groups showed the higher content collagen fibers and lower presence apoptotic osteocytes (positive caspase-3 immunoreactivity) when compared with the other groups ( p <  0.05). These results suggest that both early- and late-treatments with LHMV counteract bone loss, being the early treatment more effective than the late treatment.